2005
DOI: 10.1177/0033688205055570
|View full text |Cite
|
Sign up to set email alerts
|

‘Where’, ‘In Which’, and ‘In That’: A Corpus-Based Approach to Error Analysis

Abstract: This paper analyses the use of the word where in texts written by Malay-speaking learners of English. Data from a learner corpus is compared with data from two corpora of academic writing by native English-speaker writers. Considerable over-use of where is found: this is explained as a consequence of various patterns of misuse of where and non-use of standard forms of relativization common in written academic English. Suggestions are offered as to (a) the causes of misuse and (b) teaching strategies for helpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…This could be a reason why English learners, regardless of the existence of resumptive pronouns in L1, often supply pronoun copies in their ERCs. The discovery of resumptive pronouns in the current study lends support to several previous studies (Chang 2004, Crompton 2005, Phoocharoensil 2009.…”
Section: Selectional Restriction Violationsupporting
confidence: 91%
See 1 more Smart Citation
“…This could be a reason why English learners, regardless of the existence of resumptive pronouns in L1, often supply pronoun copies in their ERCs. The discovery of resumptive pronouns in the current study lends support to several previous studies (Chang 2004, Crompton 2005, Phoocharoensil 2009.…”
Section: Selectional Restriction Violationsupporting
confidence: 91%
“…(Chang 2004, p. 14) In an examination of ERCs found in the Brunei Learner Corpus (BLC), Crompton (2005) indicated an overuse of the relative marker where. Of all the ERCs introduced by where, approximately 38.66 % (46 out of 119 tokens) were ungrammatically produced.…”
Section: Previous Related Studies On the Relative Marker Where And Enmentioning
confidence: 99%
“…Studies focusing on more specific types of errors in L2 writing have revealed much richer findings (Crompton, 2005;Hsin, 2003;Huang, 2001;Liu & Yang, 2006;Su, 2002). For instance, Su (2002) analyzed errors of three high frequency verbs (buy, wait and learn) in the interlanguage of Chinese EFL learners based on "the Chinese Learners' English Corpus".…”
Section: Literature Reviewmentioning
confidence: 99%
“…(3) How are the errors related to the students' writing performance? (4) What are the general sources for the errors?…”
Section: Literature Reviewmentioning
confidence: 99%